2022
DOI: 10.1038/s41598-021-04009-w
|View full text |Cite
|
Sign up to set email alerts
|

The sphingosine 1-phosphate receptor 2/4 antagonist JTE-013 elicits off-target effects on sphingolipid metabolism

Abstract: Sphingosine 1-phosphate (S1P) is a signaling lipid that has broad roles, working either intracellularly through various protein targets, or extracellularly via a family of five G-protein coupled receptors. Agents that selectively and specifically target each of the S1P receptors have been sought as both biological tools and potential therapeutics. JTE-013, a small molecule antagonist of S1P receptors 2 and 4 (S1P2 and S1P4) has been widely used in defining the roles of these receptors in various biological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…meningitidis invasion of hCEMC/D3 using JTE-013 at a concentration of 1 μM ( S4 Fig ). Only 1 μM was tested, as it was recently reported that treatment with 10 μM JTE-013 has significant off-target effects on SphKs [ 45 ] and 1 μM prevented significant EGFR phosphorylation 6h p.i., without affecting N . meningitidis adhesion ( S4C Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…meningitidis invasion of hCEMC/D3 using JTE-013 at a concentration of 1 μM ( S4 Fig ). Only 1 μM was tested, as it was recently reported that treatment with 10 μM JTE-013 has significant off-target effects on SphKs [ 45 ] and 1 μM prevented significant EGFR phosphorylation 6h p.i., without affecting N . meningitidis adhesion ( S4C Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…EGFR activation has been linked to c-Src activation [35] which regulates cytoskeletal rearrangement known to be essential for N. meningitidis uptake in BECs [37]. We therefore determined the role of S1PR2 in N. meningitidis invasion of hCEMC/D3 using JTE-013 at a concentration of 1 μM (S4 Fig) . Only 1 μM was tested, as it was recently reported that treatment with 10 μM JTE-013 has significant off-target effects on SphKs [45]…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Will sphingosine kinase inhibitors alter HuNoV infection? 3) Recently, a group showed that JTE-013 has off-target effects inhibiting sphingosine kinases and dihydroceramide desaturase 1 (38). Will measurements of HIE cellular lipids after JTE-013 treatment reveal lipid changes that may affect infection?…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that S1PR2 inhibitors could enhance currently available EGF receptor inhibitors as therapeutic targets in OSCC patients. Further work should also identify any potential off-target effects of S1PR2 inhibitors and this has also been proposed in other cell types [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%